Processo de projeto de segurança contra incêndio para edifícios residenciais multifamiliares com altura superior a 12 metros - Gabriel, Helena Reginato (2020)
Considering the civil construction context – marked by the constant technological progress, diversity of specialties, and professionals involved, as well as by the complexity of the existing technical and bureaucratic processes –, it is observed the increasing valorization of the design logic executed in an integrated manner. This approach covers a comprehensive and systemic view of the design process, to encourage interaction and communication among the various agents involved and, consequently, to guarantee the quality of projects and processes. The Fire Safety Design is one of the specialties of a construction project, which has a wide complexity due to its legal requirements and demands considerable integration with other projects components, especially with the architecture design. In this sense, the present research aims to map the Fire Safety Project Process in buildings with height over 12 meters in the Rio Grande do Sul (RS) state, systematizing phases and activities, to identify which actions are part the process, how it should be done, when it should occur and who is involved in the process. For this purpose, the collection of information in reference bibliographies, as well as in the pertinent legislation, were taken as a basis to compile the data and organize the activities in an integrated Fire Safety Design process model. It is hoped that such contribution will help students and professionals in the design practice, both in terms of product development and in the management of the process.